AN ANALYSIS OF GRAMMATICAL COHESION IN “DONALD TRUMP'S SPEECH AT LIBERTY UNIVERSITY GRADUATION EVENT” - Arie Ananda Putra; Gaguk Rudianto (PROJECT (Professional Journal of English Education), 2024)
This research aims to determine the type of grammatical cohesion devices used in the text of Donald Trump's speech from YouTube videos. To find out how references, substitutions, ellipses and conjunctions are used to describe the cohesion used in the text of the speech delivered by Donald Trump. This study uses a qualitative method. Researchers identified (4) types of grammatical cohesion that play an important role in maintaining relationships between parts of the text. (4) The types of cohesion are referential cohesion, substitution cohesion with (5) data analysis, ellipsis cohesion with (5) data analysis, conjunctional cohesion with (4) data analysis, and reference cohesion with (6) data analysis. In this article, the author uses Halliday and Hasan's theory while emphasizing the importance of cohesion in maintaining smoothness and connection between text units. This article makes an important contribution to understanding and analyzing cohesion in language, thus becoming the basis for further studies regarding the grammatical aspects of cohesion in texts.